Genes Regulating Spermatogenesis and Sperm Function Associated With Rare Disorders - Linn, Emma; Ghanem, Lillian; Bhakta, Hanisha; Greer, Cory; Avella, Matteo (Frontiers in Cell and Developmental Biology, 2021)
Spermatogenesis is a cell differentiation process that ensures the production of the fertilizing sperm, which ultimately fuse with the eggs to form a zygote. Normal spermatogenesis relies on Sertoli cells, which preserve cell junctions, while providing nutrients for male germ cells’ mitosis and meiosis. Several genes regulate normal spermatogenesis, some of which are not exclusively expressed in the testis, and control multiple physiological processes in an organism. Loss-of-function mutations in some of these genes result in spermatogenesis and sperm functionality defects, and may lead as well to the insurgence of rare genetic disorders. To identify genetic intersections between spermatogenesis and rare diseases, we screened public archives of human genetic conditions (the Genetic and Rare Diseases Information Center (GARD), the Online Mendelian Inheritance in Man (OMIM), and the Clinical Variant (ClinVar)), and after extensive literature search, we identified 23 distinct genes associated with 22 rare genetic conditions and defective spermatogenesis, or sperm function. These protein-coding genes regulate Sertoli cells development and function during spermatogenesis, checkpoint signaling pathways at meiosis, cellular organization and shape definition during spermiogenesis, sperm motility and capacitation at fertilization. A number of these genes regulate folliculogenesis and oogenesis as well. For each gene, we review the genotype-phenotype association, together with associative or causative polymorphisms in humans, and provide a description of the shared molecular mechanisms that regulate gametogenesis and fertilization obtained in transgenic animal models.